What are the acceptances and associated influences of hospice care in Mainland China? A national cross-sectional study - Zhang, Xinyue; Zhang, Xun; Li, Yiqi; Chen, Tianle; Siow, Lixuen; Ye, Xinxin; Wang, Yinlin; Wang, Yujia; Ming, Wai-Kit; Sun, Xinying; Xiang, Ze; Wu, Yibo; et al. (Frontiers in Public Health, 2022)
Background China ranks 53rd out of 81 countries in the Quality of Death Index for 2021. Although hospice care demand is increasing, the progress remains slow. It is of great significance to explore the acceptances and associated influencing factors of hospice care. Methods A cross-sectional survey by quota sampling was conducted in China from July 10th to September 15th, 2021. We collected demographic data and hospice care acceptance. A stepwise linear regression analysis was used. Results This survey contained 11,031 valid questionnaire results to investigate the hospice care acceptance. It was found that individuals with undergraduate or above (β = 0.04), more properties [2 (β = 0.02), 3 (β = 0.01)], and higher reimbursement types of medical insurance [employee health insurance and commercial health (β = 0.03), government insurance (β = 0.04)] had higher hospice acceptance willingness, while males (β = −0.02) were less willing to accept than females. Psychological conditions [mild anxiety (β = 0.03), moderate anxiety (β = 0.01), moderate stress (β = 0.05), and severe stress (β = 0.06)] also played an important role. The Self-Management Scale (SHMS) (β = 0.12), EuroQol Five Dimensions Questionnaire (EQ-5D) (β = 0.05), EuroQol Visual Analog Scale (EQ-VAS) (β = 0.21), Short-Form Family Health Scale (FHS-SF) (β = 0.12), higher scores of the Short-Form Health Literacy Instrument (HLS-SF12) (β = 0.16), and Perceived Social Support Scale (PSSS) (β = 0.10) also contributed. Gender subgroup showed that in the male group, age, highest educational level, marital status, number of properties, whether having children, psychological conditions, the SHMS, EQ-5D, EQ-VAS, HLS-SF12, and PSSS showed significant difference. Urban and rural subgroups showed that age, highest educational level, number of properties, whether having chronic disease or psychological conditions, the SHMS, EQ-VAS, HLS-SF12, and PSSS were contributing factors in rural areas. Conclusion The average score of acceptance of hospice care was 65.02 points. Gender, house, anxiety, pressure, social support, and health literacy were the main influencing factors on residents' attitudes.